Oral health in end‐of‐life patients: A rapid review. (19th July 2018) - Fitzgerald, Richard; Gallagher, Jennifer
Abstract: Introduction: Maintaining oral health is vital for every individual's quality of life. Little consideration, however, has been given to the oral health of patients approaching end‐of‐life, perhaps due to sensitivities over research ethics. The aim of this rapid review is to synthesize existing evidence on oral health in this population. Methods and results: A rapid review of the literature was conducted using the key words: "Oral/Dental Health" in "End‐of‐life" or "Palliative care" patients. Nineteen articles met the inclusion criteria: five retrospective cohort studies, ten cross sectional studies, two experimental studies, one systematic review, and one audit. Quality was medium to low. The prevalence of oral/dental conditions was high in the end‐of‐life population, as were self‐reported symptoms, and poor OHRQOL. Staff placed value on oral health but identified several barriers to providing both routine daily and professional dental care. Professional oral care was beneficial in relieving palliative specific conditions and providing guidance/training for daily care. Conclusion: There is a paucity of high quality research in relation to oral health at end‐of‐life. The existing literature suggests that oral health and oral health related quality of life are poor and professional support and care for this population is needed.